Pengaruh Kompetensi Pedagogik dan Profesional Guru Terhadap Pengambilan Keputusan dalam Proses Pembelajaran di SD Negeri 060874 Medan - Zuraida Lubis; Aman Simaremare; Parlaungan Lubis (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2025)
This study aims to determine the influence of pedagogic competence and professional competence of teachers on decision-making in the learning process in SD Negeri 060874 Medan. This study uses a quantitative approach with an associative method. The research population amounted to 22 teachers, which were also used as samples with total sampling techniques. Data were collected using a Likert scale questionnaire and analyzed through multiple linear regression. The results showed that (1) pedagogic competence had a significant effect on learning decision-making (β = 0.413; Sig. = 0.004), (2) professional competence also had a significant effect on learning decision-making (β = 0.357; Sig. = 0.008), and (3) simultaneously both had a significant effect (F = 18.924; Sig. = 0.000) with a contribution of 65.9%. These results indicate that teachers who have high pedagogic and professional competence will be able to make learning decisions that are effective, reflective, and in accordance with the characteristics of students